Nowoczesna gospodarka wymaga eksperckiego samorządu gospodarczego. Wprowadzenie do modelu sektorowego - Marciniak, Piotr (PRAWO i WIĘŹ, 2025)
The 21st-century economy is experiencing unprecedented growth and specialisation, requiring an appropriate evolution in regulatory and institutional frameworks. This challenge also extends to business environment organisations, necessitating changes to their structure, objectives and functions. Against this backdrop, the author examines the shortcomings of the continental model and puts forward the sectoral model as an alternative, emphasising its potential for specialised expertise and its capacity for the extensive decentralisation of both authoritative and non-authoritative public functions.